Aberrations in ion channels interacting with lipid metabolism and epithelial–mesenchymal transition in esophageal squamous cell carcinoma - Parthasarathi, K. T. Shreya; Mandal, Susmita; George, John Philip; Gaikwad, Kiran Bharat; Sasidharan, Sruthi; Gundimeda, Seetaramanjaneyulu; Jolly, Mohit Kumar; Pandey, Akhilesh; Sharma, Jyoti (Frontiers in Molecular Biosciences, 2023)
Esophageal squamous cell carcinoma (ESCC) is most prevalent malignant gastrointestinal tumors. Ion channels contribute to tumor growth and progression through interactions with their neighboring molecules including lipids. The dysregulation of membrane ion channels and lipid metabolism may contribute in epithelial to mesenchymal transition (EMT) leading to metastatic progression. Here, transcriptome profiles of patients with ESCC were analyzed by performing differential gene expression and weighted gene co-expression network analysis to identify the altered ion channels, lipid metabolism and EMT-related genes in ESCC. 1081 differentially expressed genes including 113 ion channels, 487 lipid metabolism-related and 537 EMT-related genes were identified in patients with ESCC. Thereafter, EMT scores were correlated with altered co-expressed genes. The altered coexpressed genes indicated a correlation with EMT-signatures. Interactions between 22 ion channels with 3 hub lipid metabolism and 13 hub EMT-related proteins were determined using protein-protein interaction networks. A pathway map was generated to depict deregulated signaling pathways including insulin resistance and estrogen receptor-Ca 2+ signaling pathway in ESCC. Relationship between potential ion channels and 5-year survival rates in ESCC were determined using Kaplan Meier plots and Cox proportional hazard regression analysis. Inositol 1, 4, 5-trisphosphate receptor, type 3 (ITPR3) was found to be associated with poor prognosis of patients with ESCC. Additionally, drugs interacting with potential ion channels including GJA1 and ITPR3 were identified. Most likely, understanding alterations in ion channels with lipid metabolism and EMT in ESCC pathophysiology would provide potential targets for the better treatment of patients with ESCC.